Heritage, Reconciliation and Cross-Border Cooperation in Cyprus. Issue 1 (1st March 2021) - Reid, Amy
Abstract: Cultural heritage in Cyprus has been a contentious issue throughout the island's tumultuous history. The official partition of the island in 1974, after years of conflict between the Greek and Turkish Cypriot communities, has resulted in the destruction and neglect of heritage sites on both sides of the Cypriot 'border'. However, in recent years there has been an increase in organisations that aim to use heritage as a tool to unite both communities. This contribution examines the work of one such organisation, the Technical Committee on Cultural Heritage in Cyprus (TCCH).